2023
DOI: 10.1521/pedi.2023.37.2.262
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Heterogeneity of Schema Therapy

Abstract: We aimed to explore the heterogeneity of schema therapy regarding (a) patient characteristics, (b) content, and (c) way of delivering schema therapy. A search was conducted of the electronic databases EMBASE, PsycINFO, Web of Science, MEDLINE, and COCHRANE up to June 15, 2022. Treatment studies were eligible if they (a) used schema therapy as (component of) the intervention examined, and (b) reported an outcome measure quantitatively. A total of 101 studies met the inclusion criteria, including randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The results supported schema therapy's efficacy in reducing symptoms and improving quality of life. Schema therapy has demonstrated strong feasibility and has been successfully utilized in treating a range of psychiatric disorders, yielding positive results (van Dijk et al, 2023). Early maladaptive schemas are relevant in clinical settings beyond personality disorders (Bär et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The results supported schema therapy's efficacy in reducing symptoms and improving quality of life. Schema therapy has demonstrated strong feasibility and has been successfully utilized in treating a range of psychiatric disorders, yielding positive results (van Dijk et al, 2023). Early maladaptive schemas are relevant in clinical settings beyond personality disorders (Bär et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…ST has been proven effective for younger adults in several studies (Bamelis et al, 2014; Giesen‐Bloo et al, 2006; van Dijk et al, 2023), and there is emerging evidence that ST can also be effective for older adults (van Dijk et al, 2022; Videler et al, 2014, 2018, 2021), although in clinical practice, therapeutic nihilism still prevails towards treatment of personality disorders in later life (Penders et al, 2020; Videler et al, 2020). Individual ST was found to be an effective treatment for older adults with cluster C personality disorders (Videler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread use, and to the best of our knowledge, no research has been conducted on the effectiveness of day treatment GST for PDs. A recent systematic review of ST with a total of 101 studies (N = 4006) performed between 2000 and 2022 showed that 70% of the studies was performed among outpatients, approximately 25% was performed among inpatients (40% in prisons and 12% in nursing homes) and only three studies were performed in a day treatment setting (van Dijk et al 2023). More specifically, one of these studies focused on patients with chronic anorexia (George et al 2004); another study did not investigate ST interventions, but the effect of day treatment, with an interpersonal and cognitive behavioural approach, on EMS (Welburn et al 2000); and the third study concerned a 1-year ST with a 5-day-a-week treatment programme, where patients with severe PDs resided on weekdays and returned home on weekends.…”
mentioning
confidence: 99%